Studi Komparasi Strategi Think Pair Share (TPS) dengan Survey, Question, Read, Recite, Review (SQ3R) Terhadap Hasil Belajar IPA Siswa Kelas IV di SDN 02 Selokaton, Karanganyar Tahun 2015/ 2016 - Pamikatsih, Errin (2016)
The purpose of this study to determine: (1) The difference in the effect of the strategy of TPS with SQ3R the learning outcomes IPA fourth grade students at SDN 02 Selokaton Karanganyar, (2) Which greater influence between strategy TPS with SQ3R on learning outcomes of science students in the class IV SDN 02 Selokaton Karanganyar. Quantitative research with experimental design, the research subject is class IVA and IVB grade SDN 02 Selokaton, Karanganyar. Data collection techniques in the form of technical documentation and tests. Data were analyzed using t-test technique which preceded the prerequisite test analysis is the normality test and homogeneity test. Data analysis with a significance level of 0.05 obtained t ≤ ≤ table = -2.123 -2.000. By comparison the average value for the strategy SQ3R with 68.33 TPS strategy> 59,35.Jadi conclusion of this study is a strategy-Question Survey-Read-Recite-Review (SQ3R) has a better effect than strategy Think-Pair- Share (TPS) on learning outcomes fourth grade science students at SDN 02 Selokaton, Karanganyar Year 2015/2016. Keywords: Strategy Think-Pair-Share, Strategy Survey-Question-Read-Recite-Review, Learning Outcomes